2020
DOI: 10.1177/0192623320911606
|View full text |Cite
|
Sign up to set email alerts
|

A Pathology Review of the Lower Gastrointestinal Tract in Relation to Ulcerative Colitis in Rats and Cynomolgus Macaques Treated With Ammonium Perfluorooctanoate

Abstract: Among many short-term, subchronic, and chronic toxicology studies with ammonium perfluorooctanoate (PFOA), the gastrointestinal tract has not been identified as a target organ for PFOA-related toxicity in laboratory animals where the corresponding serum PFOA concentrations typically approach several orders of magnitude higher than the general human population. These lack of gastrointestinal tract-related findings were in direct contrast to an epidemiological observation where a positive trend was observed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Notably, PFCs have long half-life once absorbed into the blood, ranging from several weeks to a few years in humans (Olsen et al, 2007). Studies have shown that both professional and nonprofessional exposure sources contribute to the body burden of PFOS for people (Chang et al, 2020;Wang et al, 2018). Available data from the Environmental Protection Agency (EPA) on the US population exposure to PFCs have been estimated as 6 million individuals affected by PFOS, PFOA from public drinking water at levels above the 70 pg/ml dose recommended by the EPA (Hu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, PFCs have long half-life once absorbed into the blood, ranging from several weeks to a few years in humans (Olsen et al, 2007). Studies have shown that both professional and nonprofessional exposure sources contribute to the body burden of PFOS for people (Chang et al, 2020;Wang et al, 2018). Available data from the Environmental Protection Agency (EPA) on the US population exposure to PFCs have been estimated as 6 million individuals affected by PFOS, PFOA from public drinking water at levels above the 70 pg/ml dose recommended by the EPA (Hu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, PFCs have long half-life once absorbed into the blood, ranging from several weeks to a few years in humans (Olsen et al, 2007). Studies have shown that both professional and nonprofessional exposure sources contribute to the body burden of PFOS for people (Chang et al, 2020;Wang et al, 2018). Available data from the Environmental Protection Agency (EPA) on the US population exposure to PFCs have been estimated as 6 million individuals affected by PFOS, PFOA from public drinking water at levels above the 70 pg/ml dose recommended by the EPA (Hu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%